Reconfigurable and Recyclable Photoactuators Based on Azobenzene-Containing Polymers - Chen, Mingsen; Liang, Shuofeng; Liu, Chengwei; Liu, Yuanli; Wu, Si (Frontiers in Chemistry, 2020)
Photoactuators are promising smart materials that can adapt their shapes upon light illumination. Smart materials with recycling, reusable, and reconfigurable properties are crucial for a sustainable society and important to expand their function. Recently, much effort was made to address the issue of reprocessability and recyclability of photoactuators. Based on the development of polymer chemistry, supramolecular chemistry, and dynamic covalent chemistry, it is now possible to prepare reconfigurable and recyclable photoactuators using azobenzene-containing polymers (azopolymers). Herein, the recent advances on reconfigurable and reprocessable photoactuators, including dynamic crosslinked networks systems and non-covalently crosslinked azobenzene-containing polymers were reviewed. We discuss the challenges in the field as well as the directions for the development of such photoactuators.